ANALISIS PENGARUH KUALITAS MANAJEMEN PENANGANAN KELUHAN PELANGGAN DAN E-SERVICE QUALITY TERHADAP LOYALITAS DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING: Studi pada Pengguna E-commerce C2C Bukalapak - Prasetya, Adhitya Yoga; Wardati, Emi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
This paper develops a research model to examine the relationshipamong e-service quality, quality customer problem management, customersatisfaction and customer loyalty. Data from a survey of Bukalapakcustomers were used to test the research model. Confirmatory factoranalysis was conducted to examine the reliability and validity of themeasurement model, and the structural equation modelling technique wasused to test the research model. The analytical results showed that thedimensions of e-service quality, quality customer problem management,affect overall customer satisfaction and customer loyalty. Moreover, thelatter in turn are significantly related to customer customer loyalty.